2019
DOI: 10.36479/jhe.v6i2.127
|View full text |Cite
|
Sign up to set email alerts
|

The design and usage of a portable incubator for inexpensive in-field water analysis

Abstract: Humanitarian engineers need an inexpensive, fast, visually compelling way to assess bacterial water quality in remote locations. One way to do this is with 3M Petrifilm E. coli/Coliform (EC) Count Plates to detect E. coli in water samples. These require incubation at close to body temperature. To meet this need, we provide a free, open-source design of a battery-powered incubator capable of maintaining 35°C ± 1°C for up to 65 hours in ambient temperature of 25°C. Our incubator, called the Armadillo, can be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…To minimize temporal degradation, environmental samples would ideally be processed as soon as they are collected. Several studies have investigated the use of microbiological testing during field assessments and in low-resource settings (10)(11)(12)(13)(14), employing products such as Petrifilms TM (3M TM ). However, these studies often lacked a strong microbiological foundation and comparisons to standard techniques.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To minimize temporal degradation, environmental samples would ideally be processed as soon as they are collected. Several studies have investigated the use of microbiological testing during field assessments and in low-resource settings (10)(11)(12)(13)(14), employing products such as Petrifilms TM (3M TM ). However, these studies often lacked a strong microbiological foundation and comparisons to standard techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found high rates of variability within and between the methods leading to low confidence in the results (12,15). There is a clear need for the development of robust methods to incubate bacteria in the field leading to timely, reliable and reproducible quantification of bacteria in water samples (11,14,(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations